Digital Marketing Mix Is A Facelift Of Traditional Marketing Mix - Suman Devi (Elementary Education Online, 2023)
The marketing mix was developed during the early stages of the marketing concept, when physical items, physical distribution, and mass communication were the most important factors. The marketing mix paradigm, in its renowned version of the 4 Ps, has been the subject of debate both in academic literature and in management practice throughout the growth of marketing theory. Digital business is the most current of the business settings in today's era of revolutionary change, and it has the greatest requirement for differentiation and up-gradation of the mix. Throughout this evolutionary process, researchers have expressed their opinions on whether the 4 Ps paradigms can adapt to environmental changes by integrating new aspects within each "P," and whether the 4 Ps paradigm is obsolete and new paradigms should be proposed. This paper aims to clarify these two approaches to marketing mix evolution by reviewing the main literature on Digital Marketing mix and its constituents, which provides an upgrade to the existing elements of marketing mix, as well as focusing on the development of marketing mix theory for the digital context. The study focuses on the factors that lead to a customer's preference for digital purchasing, which include, in addition to the usual marketing mix, the following blends: portability, performance, payment, and privacy. This study will pave the road to view Digital Marketing as an innovative means to customer delight in the context of the warfare between upstart internet merchants and old brick and mortar stores